2007
DOI: 10.1007/s11010-007-9669-1
|View full text |Cite
|
Sign up to set email alerts
|

Na+/H+ exchange inhibition with cariporide prevents alterations of coronary endothelial function in streptozotocin-induced diabetes

Abstract: Hyperglycemia encountered during diabetes triggers abnormalities of vascular function associated with cell acidosis and calcium overload. The purpose of this study was to determine, whether Na+/H+ exchanger (NHE-1) inhibition by cariporide protects coronary cells against the deleterious effect of hyperglycemia in the rat. In vivo hyperglycemia was triggered by streptozotocin injection. One week after, the glycemia was checked and the control and diabetic animals were treated or not with cariporide (2.5 mg/kg/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…In our study, DM impaired endothelium independent relaxation that is in accordance with other reports (27-29). Since relaxation to SNP (NO donor) was shown to be impaired, it is possible that vascular smooth muscle did not respond to NO.…”
Section: Discussionsupporting
confidence: 94%
“…In our study, DM impaired endothelium independent relaxation that is in accordance with other reports (27-29). Since relaxation to SNP (NO donor) was shown to be impaired, it is possible that vascular smooth muscle did not respond to NO.…”
Section: Discussionsupporting
confidence: 94%
“…However, this status is transient: heart failure inexorably develops [ 6 ] due to the progressive development of post-prandial hyperglycemia and oxidative stress. These changes alter coronary microvessel function [ 7 ], reduce myocardial perfusion and decrease cardiac mechanical function.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia is associated with stimulation of Na+/ H+-exchanger-1 [22,38]. In the diabetic kidney it has been demonstrated that Na+/H+-exchanger-3 activity is increased [22].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia and increased metabolic rate could accentuate proton production and lead to increased proton efflux through Na+/H+ exchange, which would stimulate Na + /Ca 2+ exchange and calcium overload [38]. Imbalance of sodium and calcium with hyperglycemia is associated with endothelial dysfunction and apoptosis [38], proliferation of vascular smooth muscle cells [43], retinal microangiopathy and ischemic damage [18,44], and myocardial damage [45][46][47]. It has been shown that inhibition of Na+/H+-exchanger-1 yields beneficial effects on diabetes vascular, retinal and renal complications but until our studies no information was available whether inhibiting Na+/H+-exchanger-1 improves diabetic peripheral neuropathy [10,18,22].…”
Section: Discussionmentioning
confidence: 99%